A comparative study of lubricated friction and wear behaviour of Al–25Zn–3Cu–3Si bearing alloy. (August 2014) - Bican, Osman; Savaşkan, Temel
Lubricated friction and wear behaviour of Al–25Zn–3Cu–3Si alloy was investigated on a block-on-disc test machine in comparison with 60/40 brass and SAE 65 bronze. T6 heat treatment increased the hardness, strength and wear resistance of the Al–25Zn–3Cu–3Si alloy. This alloy exhibited much higher wear resistance than the 60/40 brass and SAE 65 bronze in both as-cast and heat-treated conditions. The results obtained from the experimental alloys are discussed in terms of their microstructure, mechanical properties and wear behaviour.